Effects of a novel weight-loss combination product containing orlistat and resveratrol on obesity: A multicenter randomized controlled study (EC-FIT) - Khin Maung Win; Tint Swe Latt; Aung Hlaing Bwa; Khin Maung Aye; Kyaw Soe Tun; Hardik Gandhi (Endocrine and Metabolic Science, 2025)
Background: Orlistat, a weight loss medication, is often less effective due to poor adherence to the dietary and exercise recommendations. However, its effectiveness is often compromised by poor adherence to recommended lifestyle changes and side effects like steatorrhea. Combining orlistat with resveratrol may enhance weight loss and offer additional metabolic benefits. Objective: This study evaluated the real-world efficacy and safety of orlistat combined with resveratrol versus orlistat alone in overweight or obese individuals in Myanmar. Method: Obese adults (BMI ≥ 25 kg/m2) were randomized into two groups for a 12-week study. The Orlistat (O) group received orlistat 120 mg three times daily, while the Orlistat & Resveratrol (O-R) group took orlistat 120 mg plus resveratrol 100 mg thrice daily. Primary outcome measured was weight change; secondary outcomes included Total Cholesterol, LDL-cholesterol, Blood pressure, HbA1c, alanine transaminase (ALT), controlled attenuation parameter (CAP), Liver stiffness, and Total Body Fat. Adverse events were also recorded. Result: The O-R group lost more weight (−3.31 kg, 95 % CI: 2.36–5.04, p < 0.001) than the O group (−2.92 kg, 95 % CI: −2.6442–4.5471, p < 0.001). Additionally, the O-R group showed greater reductions in total body fat (−4.93 %), diastolic blood pressure (78.38 mmHg vs 75.93 mmHg; 95 % CI: 0.4473–4.4707, p < 0.05), and CAP score (276.62 dB/m vs 253.16 dB/m; 95 % CI: 8.46–38.85, p < 0.05). Significant weight loss in the O-R group was observed in obese patients with steatosis (S1–S3) or fibrosis (F2–F4), and in diabetic patients, particularly those with a BMI ≥30 (−2.79 kg vs −1.04 kg, p < 0.05) and steatosis (−2.17 kg vs −0.44 kg, p < 0.05). Steatorrhea occurred in both groups, while diarrhoea was noted only in the O group. Conclusion: Addition of resveratrol to orlistat provides synergistic benefits to weight loss with additional benefit in terms of reducing total body fat and diastolic BP. These benefits were also apparent in subgroup of patients with diabetes suffering from obesity or steatosis.Trial registration number: ISRCTN10642495.